ДОСЛІДЖЕННЯ ВПЛИВУ ЗМІНИ ПАРАМЕТРІВ БЕЗКОНТАКТНИХ МАГНІТО-ЕЛЕКТРИЧНИХ ДВИГУНІВ ЗВОРОТНО-ОБЕРТАЛЬНОГО РУХУ НА ЇХ ХАРАКТЕРИСТИКИ - Акинін, К.П.; Кіреєв, В.Г.; Пєтухов, І.С.; Філоменко, А.А.; Лавриненко , В.А.; Міхайлик , О.М. (Інститут електродинаміки Національної академії наук України, 2022)
The paper presents the results of studies of the influence of changing the parameters of a specialized brushless magnetoelectric motor on its characteristics in the mode of return-rotary motion. The frequency dependences of the amplitude of the rotor oscillation angle, the effective value of the stator current, the efficiency index of the motor operation mode, the amplitude of the angular speed of the rotor oscillations, the amplitude of the stator voltage, the total value of losses in the motor are given. The dependences of the resonant frequency of mechanical oscillations on the changing values ​​of the elasticity coefficient, the moment of inertia, as well as temperature-dependent parameters are determined. The dependence of the maximum value of the efficiency of the return-rotary motion motor on the viscosity coefficient of the mechanical load is obtained. It is shown that the most economical mode of operation of the motor is provided under the condition of resonance of mechanical oscillations.  Reference 11, figure 5.